Injuries among Talented Young Dancers: Findings from the UK Centres for Advanced Training - Steinberg, N.; Aujla, I.; Zeev, A.; Redding, E. (International Journal of Sports Medicine, 2014)
The aim of the present study was to characterize the injuries of young dancers attending Centres for Advanced Training. 806 dancers, ages 10–18 years responded to surveys regarding their biological profile, dance experience and injury history, and were examined for their anthropometric profile. Of the 806 dancers, 347 reported an injury. Based on 4 age groups, the total hours of practice per week increased significantly with increasing age. Incidence of injuries per 1 000 h of dance practice for dancers ages 11–12 were found to be significantly higher compared to the incidence for dancers ages 13–18 (p<0.05). Foot and ankle and other lower extremities were the most common injury location, and muscle injuries were the most common type of injury. Total months in CAT training (OR=1.044, 95% CI=1.014–1.075) and hours per week in creative style practice (OR=1.282, 95% CI=1.068–1.539) were found to be significantly associated with injuries. In conclusion, both young and mature dancers are exposed to extensive risk of injury. The intensity of training (such as number of months and number of hours of training per week) is important factor that should be taken into account in order to decrease future injuries among young dancers.
Keywords: dancing; injuries; dance experience; body structure